Particle Number Measurement and Its Numerical Simulation of the Airborne Particle Counter by 'Post-Collection-Check'. Issue 1 (1st August 2022) - Gao, Z L; Zeng, G L; Cheng, Q D; Wang, R J; Zhang, W H; Wang, F Q; Chen, J; Wu, J P; Guo, J
Abstract: The measurement results of the light-scattering airborne particle counter can effectively evaluate the concentration of airborne particles in the clean environment and confined space, and the accuracy improvement of the calibration measurement results has attracted more and more attention. This paper introduces the 'post-collection-check' way of the airborne particle concentration measurement method of the OPC (Optical Particle Counter), based on FESEM (Field Emission Scanning Electron Microscopy) and AAO (Anodic Aluminum Oxide) template, the probability distribution of the collected PSL (Polystyrene Latex) particles on the surface of AAO template, and the pressure parameters of AAO template under the different particle over current areas are both simulated. The numerical simulation results will help to improve the accuracy of the inference statistics of the collected PSL particle number on the membrane filter, and to give guidance on the optimal design of the PSL particle collection tube and the membrane filter, in order to provide an important reference for further improving the OPC particle concentration calibration and traceability method based on statistical theory.